Analyzing the Role of Apparel E-Retailer’s Brand Reputation in Moderating the Influence of Social Media Marketing and Electronic Word of Mouth - Dewantoro, Faishal Zuhair Bimo; Nurdin Sobari (Management Analysis Journal, 2024)
This study aims to explore how social media marketing (SMM) and electronic word of mouth (eWOM) influence consumers' online purchase intentions, considering the mediating role of conviction and the moderating role of e-retailer apparel brand reputation. Using a quantitative approach, the study collected primary data through a questionnaire distributed to 300 respondents familiar with the Erigo brand, employing random sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Smart PLS software. The findings reveal that SMM significantly impacts conviction, while eWOM shows a positive but insignificant effect. Conviction has a positive but insignificant impact on online purchase intention (OPI), though it mediates the effect of SMM on OPI. However, conviction does not significantly mediate the relationship between eWOM and OPI. SMM and eWOM have direct significant effects on OPI, with brand reputation moderating the influence of SMM and eWOM on OPI through conviction. This research offers valuable insights for decision-makers, particularly in leveraging social media marketing and eWOM strategies to optimize business effectiveness and efficiency. Startup companies in the digital industry can benefit from these strategies by considering conviction and brand reputation as critical factors. Limitations include the relatively small respondent pool of 300 and the need for broader population analysis and deeper exploration of blue ocean strategies for startups.